Interpreting Chinese concepts of authenticity: A constructivist epistemology - Cheng, Denian; Fountain, Joanna; Rosin, Christopher; Lucock, Xiaomeng (Tourism management (1982), 2024)
Authenticity is one of the central components of the tourist experience and has been the subject of substantial academic research. Despite this attention, debate on the notion is ongoing. This paper aims to enhance the analytic potential of the largely Western-centric notion of authenticity by examining the value and meaning of Suzhou food authenticity, from the perspective of producers and suppliers of food and food tourism experiences. Using semi-structured interviews, participant observation and documentary analysis, this study finds that the broad notion of authenticity has considerable relevance to supply-side stakeholders' perceptions of food tourism experiences in Suzhou, however in describing certain foods, local stakeholders do not use a term that directly translates to "authentic", and instead rely on many other Chinese concepts and expressions to authenticate food attractions and experiences. This study confirms the significance of authenticity to food tourism experiences from the producer and supplier perspective but also suggests that authenticity is a culturally specific notion and, fundamentally, there is great utility in applying a constructivist epistemology to study the Chinese concepts of authenticity.